BDNF signaling and survival of striatal neurons - Baydyuk, Maryna; Xu, Baoji (Frontiers in Cellular Neuroscience, 2014)
The striatum, a major component of the basal ganglia, performs multiple functions including control of movement, reward, and addiction. Dysfunction and death of striatal neurons are the main causes for the motor disorders associated with Huntington’s disease (HD). Brain-derived neurotrophic factor (BDNF), a member of the neurotrophin family, is among factors that promote survival and proper function of this neuronal population. Here, we review recent studies showing that BDNF determines the size of the striatum by supporting survival of the immature striatal neurons at their origin, promotes maturation of striatal neurons, and facilitates establishment of striatal connections during brain development. We also examine the role of BDNF in maintaining proper function of the striatum during adulthood, summarize the mechanisms that lead to a deficiency in BDNF signaling and subsequently striatal degeneration in HD, and highlight a potential role of BDNF as a therapeutic target for HD treatment.